-0.10(28)+0.30x=0.05(x-6)

Simple and best practice solution for -0.10(28)+0.30x=0.05(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.10(28)+0.30x=0.05(x-6) equation:


Simplifying
-0.10(28) + 0.30x = 0.05(x + -6)

Multiply -0.10 * 28
-2.8 + 0.30x = 0.05(x + -6)

Reorder the terms:
-2.8 + 0.30x = 0.05(-6 + x)
-2.8 + 0.30x = (-6 * 0.05 + x * 0.05)
-2.8 + 0.30x = (-0.3 + 0.05x)

Solving
-2.8 + 0.30x = -0.3 + 0.05x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.05x' to each side of the equation.
-2.8 + 0.30x + -0.05x = -0.3 + 0.05x + -0.05x

Combine like terms: 0.30x + -0.05x = 0.25x
-2.8 + 0.25x = -0.3 + 0.05x + -0.05x

Combine like terms: 0.05x + -0.05x = 0.00
-2.8 + 0.25x = -0.3 + 0.00
-2.8 + 0.25x = -0.3

Add '2.8' to each side of the equation.
-2.8 + 2.8 + 0.25x = -0.3 + 2.8

Combine like terms: -2.8 + 2.8 = 0.0
0.0 + 0.25x = -0.3 + 2.8
0.25x = -0.3 + 2.8

Combine like terms: -0.3 + 2.8 = 2.5
0.25x = 2.5

Divide each side by '0.25'.
x = 10

Simplifying
x = 10

See similar equations:

| 11y+16=42-2y | | 4f+13g(2w)= | | 17-8v=-3(5+8v) | | y^2-xy-56x^2= | | 3x+8y+13= | | 3x^2-12x=-9 | | y=6x-3.5 | | -5(1+4x)+1=x+38 | | -5(3p-3)-5(3-3p)=-4p-5p | | x^2+42-135=0 | | t+2=26-2t | | 30=x/7-20 | | 3(4x+4)=6(x+1)+4x | | 34+2n=8(n+5) | | 9x-(5x+9)=4x-24 | | -1/4=2.4x+10-0.35x | | 6x+7=103 | | 3x-3x=-4x | | b-2=b+6+2-10 | | x-3-8x=-24 | | 1/2(-2x-7)=3/4 | | 2x-15=3-x | | cosx^2-cosx=0 | | 8(1+5k)=8(1-7k) | | y=(-13/16)-1/4 | | 6(5x-6)=6(6x+8) | | 4y-3=2y-11 | | -3(4x-7)+3=5x-27 | | 12x+2+7x=1-8x+16 | | m^2+mn+n^2=0 | | 2(2l+w)=72 | | 28-7r=3(1+6r) |

Equations solver categories